A rare case report of eyelid basal cell carcinoma with special emphasis on its unusual presentation and role of radiotherapy as its treatment options - Gogoi, Rajendra Nath; Nandi, Sunanda; Agarwalla, Vijaya (International Journal of Research in Medical Sciences, 2020)
Basal cell carcinoma (BCC) is the most common type of skin cancer in white-skinned individuals but is rare in blacks and Indians. Skin cancers mainly affect sun-exposed areas like the neck and face (88-90%). BCC rarely metastasizes or kills, but is still considered as malignant because it can cause significant destruction and disfigurement by invading surrounding tissues. Here we present a case of BCC appearing in upper eyelid at the eyebrow region which is very rare to cite in literature. The patient was a resident of high altitude with no evidence of local invasion or distant metastasis for which she was treated with radiation therapy. Radiation therapy is a good therapeutic option in patients who are unwilling for surgery and in those requiring extensive surgery. BCC is usually not fatal, but early diagnosis and appropriate treatment promises better functionality and esthetic outcome.